Representações mobilizadas nas turmas de 3º ano do ensino médio de duas escolas da rede estadual de Itabaiana/SE no ensino de geometria analítica - Oliveira, Jones Clécio (2014)
This research investigates how and which mathematical representations are mobilized by high school students of two schools of the Itabaiana / SE state network when solving activities involving concepts of analytical geometry. In order to do so, the study is based on Duval's theory of semiotic representation records (2003, 2009, 2010), as well as on the national curricular guidelines and guidelines published in Brazil (1999, 2002, 2006) the photocopies of twenty-one (21) student books and the protocols of a sequence of activities developed with one hundred and forty-two (142) students enrolled in the classes participating in the research . Based on the data collected following the qualitative research presuppositions Lüdke and André (1986) and the principles of the content analysis Bardin (2010) it is concluded that both textbooks and activities selected by the teachers and consequently carried out by the students, for the most part, the transformation of record conversion, however, mostly emphasize in algebraic, geometric, numerical, and natural language representations. Next, we applied a teaching sequence with all two hundred twenty-seven (227) students enrolled in these classes, seeking to identify some understandings regarding the learning of analytical geometry and the registers of semiotic representation, as well as to verify if and how this content was conducted in the classroom. Based on the collected data we conclude that teachers use in their class notes the conversions between representation registers, in the same way that the questions of the LD allow the student to also use these conversions. In the analysis of the LD, we verified that the activities that use the treatment in its resolution totals 7.91%, being 79.55% of treatment in the algebraic representation, 11.36% of treatment in natural language, 6.82% in the symbolic and 2 , 27% in figural, and 15.27% in book B, accounting for 37.70% of the activities that are worked through the treatment, being 73.76% of the algebraic representation register, 13.48% in numerical, 8 , 51% in the symbolic and 4.36% in the natural language. With regard to the conversion of records, in book A the percentage is 92.09%, while book B totals 62.30%. We also emphasize that the activities present in the students' notebooks mostly use the conversion among the representations, in the students' notebooks B2 totals 93.50% of the activities analyzed in the notebook, already in the students' notebooks a1, this total is 87 , 68%. In the students' book a2 and B1, we noticed a lower percentage than the others, totaling respectively 22.91% and 23.08% of representation conversions. We emphasize the importance of this research, because there are few investigations in the state of Sergipe having as main theoretician Raymond Duval and the theory of records of semiotic representation, thus enabling the expansion of this field in our state.